Effect of Sheetali pranayama on cardiac autonomic function among patients with primary hypertension - A randomized controlled trial. (May 2020) - Thanalakshmi, J.; Maheshkumar, K.; Kannan, R.; Sundareswaran, L.; Venugopal, V.; Poonguzhali, S.
Abstract: Background: Sheetali pranayama is a cooling pranayama practiced for hypertension (HTN). The effects of Sheetali pranayama, as a solitary intervention on cardiovascular and autonomic changes in hypertension is unknown. Materials and methods: The current study was conducted on 100 patients with HTN, randomly allocated to HTN with pranayama (Intervention group, n = 50) and HTN without pranayama (control group, n = 50) group. The intervention group practiced Sheetali pranayama for a period of 3 months. Blood pressure and HRV was assessed before and after the intervention. Results: Intervention group showed a significant (P < 0.05) reduction in blood pressure variables when compared to the control group. In short term HRV, time and frequency domain parameters showed parasympathetic dominance (P < 0.05) in the intervention group. Conclusion: Sheetali pranayama significantly reduces blood pressure in patients with HTN and improved heart rate variability. Sheetali pranayama could thus be practiced in addition to regular medications for the efficacious management of HTN. Highlights: Validated yoga modules are widely prescribed in the management of hypertension and cardiovascular diseases. However, efficacy and mechanism of action of individual yoga practices is yet to be explored in detail. Sheetali pranayama, as a solitary practice, has effectively reduced blood pressure in patients with hypertension. The three month practise has also effectively restored autonomic imbalance, with no adverse effects. The translational value of the study lies in the application of yoga in hypertension and cardiovascular diseases as a complementary therapy.